QUBIC Experiment Toward the First Light - D'Alessandro, G.; Battistelli, E. S.; de Bernardis, P.; De Petris, M.; Gamboa Lerena, Martín Miguel; Grandsire, L.; Hamilton, Jean-christophe; Marnieros, S.; Masi, S.; Mennella, A.; Mousset, L.; O'Sullivan, C.; et al. (Springer/Plenum Publishers, 2022)
Fil: D'Alessandro, G.. Università degli studi di Roma "La Sapienza"; Italia